Gender Bias in the Book “Syarh 'Uqudul Lujain fi Bayani Huquq al-Zaujain” by Nawawi Al-Bantani - Alma'arif, Alma'arif; Muhajir, Muhajir (An-Nida', 2023)
This article aims to prove that the book “Syarh ‘Uqudul Lujain fi Bayani Huquq al-Zaujain,” which is studied in many Islamic boarding schools, has indications of gender bias and proves that the book ‘Uqudul Lujain is a legitimizing tool in perpetuating the construction of gender bias. This proof is very important in the midst of the movement for gender equality and justice. This understanding and awareness is very important in the midst of the struggle for gender equality and justice. The method used in this research is an intertextual, dynamic, and interactive method. The intertextual method is used to interpret existing texts and utterances from the intellectual being studied (Nawawi Al-Bantani) and find meanings by tracing the relationships between texts and utterances in the discourse. The dynamic method involves placing synchronic conditions in a diachronic context, and the interactive method involves revealing and depicting the movement of a person or group's intellectual development as a result of dynamic struggles between past and present, between and within various political and intellectual traditions, as well as between various arenas of power relations. The results of the research prove that the book ‘Uqudul Lujain by Nawawi Al-Bantani is a book that spreads gender bias (discrimination and subordination towards women) in two forms: subordination and stereotype. Nawawi Al-Bantani belongs to the category of Muslim scientists with a monodisciplinary paradigm. The monodisciplinary paradigm is in conflict with other scientific paradigms that are increasingly developing.  Abstrak: Artikel ini bertujuan membuktikan bahwa kitab “Syarh ‘Uqudul Lujain fi Bayani Huquq al-Zaujain” yang dipelajari di banyak pesantren terindikasi bias gender serta membuktikan bahwa kitab ‘Uqudul Lujain menjadi alat legitimasi dalam melestarikan konstruksi bias gender. Pembuktian ini menjadi sangat penting di tengah gerakan kesetaraan dan keadilan gender. Metode yang digunakan dalam penelitian ini adalah metode intertekstual, dinamis dan interaktif. Metode intertekstual dengan cara menginterpretasikan teks-teks yang ada dan ujaran-ujaran dari intelektual yang diteliti (Nawawi Al-Bantani) serta menemukan makna-makna dengan melacak relasi-relasi antar teks dan ujaran-ujaran yang ada dalam diskursus. Metode dinamis dengan cara menempatkan kondisi-kondisi sinkronik dalam sebuah konteks yang diakronis, dan metode interaktif dengan cara mengungkap dan melukiskan gerak perkembangan intelektual seseorang atau kelompok sebagai akibat dari pergulatan dinamis antara masa lalu dan masa kini, antar dan di dalam beragam tradisi politik dan intelektual, serta antara beragam arena relasi kuasa. Hasil penelitian membuktikan bahwa kitab ‘Uqudul Lujain karya Nawawi Al-Bantani itu adalah kitab yang menyebarkan dan mendoktrin paham bias gender (diskriminasi dan subordinasi terhadap kaum perempuan) dalam dua bentuk; subordinasi dan stereotype. Nawawi Al-Bantani termasuk kategori ilmuwan muslim yang berparadigma monodisiplin. Paradigma monodisiplin bertentangan dengan paradigma keilmuan lain yang semakin berkembang.